Studies on developing limbs in chick and mouse embryos - Goel, Suresh C. (The University of Edinburgh, 1969)
1. Differentiation of epiphyseal cartilage in developing hind limb -buds of chick and mouse has been studied, both by light and electron microscopy. Similar studies have been carried out on cartilage of chick differentiated in tissue culture. Results were also obtained by autoradiography using proline-H³ in tissue culture, cytochemistry for glycogen and RNA, and immunology. Effects of hydrocortisone on developing limbs of the chick were also studied.

2. The results indicate that during differentiation of chondrogenic cells the endoplasmic reticulum and the Golgi apparatus become very well developed. There is also a decrease in the nucleo- cytoplasmic ratio, and the nucleus no longer occupies the centre of the cell. The general electron density of the cells increases and there is a change in the outline of the cell from smooth to scalloped. Some cytosomes (i.e. vacuolar bodies which may contain vesicles or other unidentified structures) are formed.

3. The endoplasmic reticulum in chondroblasts as well as in chondrocytf-s shows three types of profile - rough cisternal, both elongated and saccular (up to c.5μ across) and smooth vesicular - all filled with moderately electron -dense amorphous material. The cisternae have been seen to be directly continuous with the outer nuclear membrane, Golgi apparatus and plasmalemma, indicating that the various components of the membrane system are to some extent interconvertible. Feed -back control of nuclear activity by the contents of the endoplasmic reticulum is suggested.

4. The juxtanuclear Golgi apparatus of cartilage cells shows three types of profile - lamellar, vesicular and large vacuolar (up to 1.2µ across). The lamellae and the vesicles contain moderately electron -dense material, but the vacuoles are usually electron- translucent in early chondroblasts and contain a chondrogen granule, in late chondroblasts and chondrocytes. The substructure of the chondrogen granule shows smaller granules with attached fibrils, which resemble similar elements of the extracellular phase.

5. The synthesis of glycogen is a feature of chondrogenesis in the epiphyseal cartilage of the mouse, and the amount of glycogen increases with progressive differentiation. In contrast, only a small amount of glycogen was seen in chick, and it was confined to a few cells of diaphysis.

6. Chondroblasts differentiated in tissue culture, as compared to those differentiated in vivo, have a greater number of cytosomes and often show some intracytoplasmic fibrils. The contents of the cytosomes are also more heterogeneous.

7. In the last stages of differentiation, two hypes of hypertrophy are found. In the mouse, there is a progressive increase in the general electron density and in glycogen content of the cells, while in the chick, the general electron density reaches a maximum in chondrocytes and decreases during hypertrophy, so that the hypertrophied chondrocytes appear rather electron - translucent; and, their cytoplasmic organelles also undergo degeneration.

8. The amount of the extracellular phase increases with progressive differentiation and is very extensive in fully -formed cartilage. In the mesenchyme the extracellular phase is hyaline, but in the fully -formed cartilage, it appears under the electron microscope as an amorphous ground substance with fibres and granules. The fibres are usually 15 - 20 imp. thick and some of them show a faint periodicity, of 9 mit in chick, and 5.5 mp. in mouse. In chick chondrogenesis the fibres appear slightly earlier than the granules. The chemical nature of the fibres and granules is discussed and it is suggested that the fibres are almost certainly collagenous, whereas the granules contain accumulations of protein- polysaccharides.

9. Synthesis and secretion of the contents of the extracellular phase have been investigated, both by autoradiographic and morphological studies, and the findings are discussed with particular reference to the contents of the Golgi vacuoles and endoplasmic reticulum, and to the process of excortication. It is suggested that, in cartilage, the non -collagenous protein, after synthesis in the endoplasmic reticulum, is combined with the polysaccharides in the Golgi apparatus and then secreted; whereas the collagen is directly secreted out of the endoplasmic reticulum.

10. The immunological studies indicate that the saline -soluble fraction of embryoni,: chick cartilage is very weakly antigenic.

11. Hydrocortisone acetate, when injected into 3 or 4-day-old chick embryos, caused necrosis in limb-bud mesenchyme (primary effect), after a further incubation of 24 hours. The necrotic centres usually appeared in the central and subapical mesenchyme. Similar treatment of 4-day-old embryos with higher doses (7.5 mg/egg) caused, in addition, haemorrhage in limb-buds, micromelia (secondary effects), and a slight retardation in growth. The mechanisms of phagocytosis and necrosis, due to hydrocortisone treatment, were investigated and are discussed.

12. The distribution of RNA in the chick limb -buds was studied, using methyl green-pyronin staining and RNAse digestion.